Pengaruh Disiplin Kerja dan Kepuasan Kerja Terhadap Kinerja Studi pada Karyawan PT. Navil Natural Organik di Bantul - Fatma Sarasti; Hardin Hardin; Agus Saur Utomo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Human resource management is a process related to the implementation of management functions. Therefore, if human resources within an organization are properly managed and utilized, the organization will be able to run its operations optimally, thereby encouraging employees to contribute positively to performance. Performance can be influenced by work discipline and job satisfaction. The purpose of this study is to examine the effect of work discipline on employee performance at PT. Navil Natural Organik and to examine the effect of job satisfaction on employee performance at PT. Navil Natural Organik. The population in this study consisted of all employees of PT. Navil Natural Organik. The sampling technique used was saturated sampling. Thus, a total sample of 115 respondents was obtained. Data were collected using questionnaires that had been tested for validity and reliability. The data analysis technique used was multiple linear regression analysis. The results show that work discipline has a positive and significant effect on the performance of employees at PT. Navil Natural Organik, and job satisfaction also has a positive and significant effect on the performance of employees at PT. Navil Natural Organik.